Parametric studies on the behaviour of reinforced elastomeric bearings considering the compressibility and extensibility index, shape factor, and lift-off. (June 2021) - Bai, Junfu; Van Engelen, Niel C.; Cheng, Shaohong
Abstract: Reinforced elastomeric bearings (REBs) are widely used in bridges as well as for seismic isolation applications. Analytical solutions for the critical design properties of REBs (e.g. compression and bending modulus, stress distributions) have been derived based on the assumptions of the pressure solution. In all cases, the analytical solutions can be expressed as functions of the dimensionless compressibility and extensibility index. This parameter accounts for the influence of the compressibility of the elastomer and the extensibility of the reinforcement. Together with the shape factor, these variables are highly influential on REB design. The objective of this study is to investigate mechanical behaviour of bonded and unbonded REBs with the same compressibility and extensibility index but different other parameters and the influence of the shape factor by finite element analysis (FEA) including lift-off. For unbonded REBs, lift-off (i.e. the separation between the superstructure and the bearings) can occur under certain combinations of large rotations and relatively low axial stress. Three different loading cases (pure compression, pure bending and the combined case) are considered. The results show that REBs with the same compressibility and extensibility index but different other parameters have similar behaviour under the same loading condition. Available analytical solutions have good agreement with numerical results provided an appropriate shear modulus is selected and the level of rotation is reasonable for structural applications.